2006
DOI: 10.1007/s00404-006-0174-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of uterine cavity by hysteroscopy in assisted reproduction programme and its influence on pregnancy outcome

Abstract: Patients with recurrent IVF embryo transfer failures after normal hysterosalpingography findings should also be reevaluated using hysteroscopy prior to further commencing IVF-embryo transfer cycles in order to enhance the clinical pregnancy rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
1
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(112 citation statements)
references
References 12 publications
4
100
1
7
Order By: Relevance
“…13 Several studies have demonstrated that hysteroscopy is more accurate than HSG. [14][15][16] The relative merits of HSG and laparoscopy in the screening for tubal pathologies have been a matter of discussion for more than 30 years. World Health Organization studies indicate that laparoscopy identifies tubal patency better than HSG.…”
Section: Discussionmentioning
confidence: 99%
“…13 Several studies have demonstrated that hysteroscopy is more accurate than HSG. [14][15][16] The relative merits of HSG and laparoscopy in the screening for tubal pathologies have been a matter of discussion for more than 30 years. World Health Organization studies indicate that laparoscopy identifies tubal patency better than HSG.…”
Section: Discussionmentioning
confidence: 99%
“…Still, there is no consensus protocol regarding the optimal number and timing of the biopsies that are needed for achieving the improvement in implantation and a large-scale prospective randomized trial is required in order to elucidate this issue. Along this line, other forms of mechanical manipulation in human, such as curettage and hysteroscopy (Friedler et al 1993, Mooney & Milki 2003, Rama Raju et al 2006, El-Toukhy et al 2009, Bosteels et al 2010, also generate a favorable effect on the pregnancy outcome in IVF patients. Taken together, these findings suggest that the success of implantation in all these cases is apparently attributed to an injury-induced inflammatory reaction that leads to the development of an adequate decidua supporting implantation.…”
Section: Local Injury To Endometrium Increases Its Receptivitymentioning
confidence: 99%
“…Hormonal imbalance between the uterus and the embryo may be a factor for implantation failure, while structural uterine abnormalities may be another [1]. While it is not possible to assess the microenvironment of the uterus, an impaired intrauterine structure can be evaluated easily by hysteroscopy [2]. Such structural abnormalities include congenital fusion defects, leiomyomas, adhesions, and endometrial polyps, the latter of which is the commonest pathology, seen at a rate of 1.4-26% in IVF patients [3][4][5].…”
Section: Introductionmentioning
confidence: 99%